EWS::FLI1-DHX9 interaction promotes Ewing sarcoma sensitivity to DNA topoisomerase 1 poisons by altering R-loop metabolism - Olmedo-Pelayo, Joaquin; Granado-Calle, Esperanza; Delgado-Bellido, Daniel; Lobo-Selma, Laura; Jordan-Perez, Carmen; Monteiro-Amaral, Ana T.; Ehlers, Anna; Ohmura, Shunya; Garcia-Dominguez, Daniel J.; Mackintosh, Carlos; Carcaboso, Angel M.; Alonso, Javier; et al. (Oncogene, 2025)
Drug resistance is an ill-defined cause of dismal outcomes in cancer. Ewing sarcoma (EwS), a pediatric cancer characterized by high therapy failure rates, is driven by a single oncogenic event generating EWSR1::ETS gene fusions (primarily EWSR1::FLI1) in a silent genomic background. This provides a straightforward model to study the impact of gene fusions on drug responses. Here, we describe a novel mechanism of sensitivity to DNA topoisomerase 1 poisons in EwS. We discovered that EWS::FLI1 prevents the resolution of R-loops induced by these drugs via sequestering DHX9 helicase, ultimately resulting in R-loop accumulation, replication stress, and genome instability. In turn, excessive DHX9 or reduced EWS::FLI1 levels render EwS cells resistant to the active metabolite of irinotecan (SN-38) independent of proliferation and global transcription rates. This resistance helps explain how elevated DHX9 levels predict worse clinical outcomes. Overall, our research demonstrates the impact of a dominant mutation on cancer drug sensitivity, highlighting its significant clinical implications.
Online verfügbar: 28. Juli 2025
Gesehen am 16.12.2025